Legal Protection Child Recidivists Under Article 69 Juvenile Criminal Justice System Law: A Case Study of Majalengka - Soni Subekti,; Wiwin Widiya Ningsih, (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
This study aims to examine the effectiveness of legal protection for repeat offenders in Majalengka Regency in relation to Article 69 of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA). However, findings in the field show that law enforcement officials in Majalengka still apply a repressive approach to repeat offenders, including imposing prison sentences under the pretext of deterrence and social pressure. This study uses a normative-empirical juridical approach by analyzing legal norms, institutional behavior, and law enforcement practices by the police, prosecutors, courts, and correctional institutions. Data was obtained through interviews, field observations, and studies of regulations and court decisions. The results of the study show a gap between the normative idealism of the SPPA and legal practices in the field, where the principle of restorative justice has not been consistently implemented. Law enforcement is still oriented towards retribution, not recovery, thus failing to nurture and reintegrate children into society. This study recommends the establishment of a Regional Regulation (Perda) on the protection of children who are repeat offenders, strengthening the role of correctional centers and social rehabilitation institutions, and training law enforcement officials on the principles of restorative justice. Theoretically, this study emphasizes the importance of a humanistic, educational, and restorative approach in the legal protection of children, in accordance with national and international standards on children's rights